Response to letter to the editor regarding "Acute mountain sickness among tourists visiting the high-altitude city of Lhasa, Tibet, China at 3658 m above sea level: a cross-sectional study" - Gonggalanzi; Per Nafstad (BMC, 2017)
Abstract We kindly thank the journal for the opportunity to respond to the recent comments made regarding our manuscript entitled "Acute mountain sickness among tourists visiting the high-altitude city of Lhasa, Tibet, China at 3658 m above sea level: A cross-sectional study".